PERILAKU KONSUMSI RUMAH TANGGA PETANI KARET DITINJAU DARI TINGKAT PENDAPATAN (Studi Kasus Masyarakat Petani Karet di Dusun Berona, Kabupaten Sekadau) (SB) - Prayoga, Aji; Basri, Muhammad; Syamsuri, Syamsuri (Universitas Tanjungpura, 2025)
This research aims to analyze the consumption behavior of rubber farmer households in Berona Hamlet, Sekadau Regency, taking into account their income level. The research method used is a qualitative approach with a case study approach. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis is carried out using the Miles and Huberman model, and data validity is checked through triangulation techniques. This research is conducted because the fluctuation of rubber prices in recent years has affected the ability of rubber farmers to meet their household needs. The research findings show that the consumption behavior of rubber farmer communities in Berona Hamlet varies depending on their income level. Each household has different income levels, which are influenced by the amount of rubber they sell and the size of the land where they farm rubber. Income from rubber farming ranges fromRp. 325,000 to 975,000 per month, which is a low income level, thus affecting their consumption patterns.